PENERAPAN FUZZY C-Means CLUSTERING sebagai PENDUKUNG SISTEM KEPUTUSAN SELEKSI PENERIMA BANTUAN SOSIAL: Desa Sukau Kayo, Lebong, Bengkulu, Indonesia - R.S, Penti Septian; Reswan, Yuza; Apridiansyah, Yovi; Sunardi, Dandi (Universitas Lampung, 2024)
Abstract. Frequently the occurrence of discrepancies in selecting eligible candidates for social assistance programmes. Thus, the research aims for creating a support system for making decisions in the selection of prospective recipients of social assistance programmes by applying the Fuzzy C-Means (FCM) method for direct assistance recipients who are eligible or not. The results obtained after testing of system on the 91% questionnaire results are very helpful in taking a decision.